Tendency in the Spread of Syphilis among the Population of Lituania, Latvia and Estonia (1920–1940) - Miltiņš, Alfreds (Acta Medico-Historica Rigensia, 1992)
А study has been made of the spread of venereal diseases in Lithuania, Latvia and Estonia from 1920-1940; it is a systematization of the features characterizing the incidence of syphilis, gonorrhea and soft chancre [l. 2,3, 7,9, 12] material presented is of a factographic character. Some suggestions in a number of cases require substantial affirmation therefore correction by analysing the course of epidemiologic process of the concrete disease has been made.